(untitled) - Kimball, Cheryl ([Irvine, CA.], 2007)
The book privides an oveview of the basic types of written sales communication situations, including sales letter strategies, style, format, and e-mail and fax; also including model letters
Keywords: Sales letters,Commercial correspondence; Handbooks, manuals, etc.,Handbooks, manuals, etc